Studies of Etichal Dimensions of Educationin Artifical Intellegence Era: A Study from A Humanism Philosophy Perspective Inspired by Carl Rogers - Yulianto, Sandi Ferdy; Rahmawati, Novi Rosita; Falach, Ghulam; Fanani, Moh. Zainal (Proceeding International Conference on Religion, Science and Education, 2024)
This study explores the ethical dimensions of education in the era of Artificial Intelligence (AI) through the lens of humanistic philosophy, drawing inspiration from the teachings of Carl Rogers. As AI technologies continue to reshape various aspects of society, including education, it is crucial to critically examine the ethical implications arising from these transformations. This research adopts a humanistic philosophy perspective, specifically emphasizing the ideals and principles advocated by Carl Rogers, to analyze the evolving landscape of education in the AI era. The study begins by providing an overview of the primary ethical concerns associated with the integration of AI into education, including issues related to privacy, bias, equity, and the commodification of knowledge. Drawing inspiration from Carl Rogers' human-centered approach to personal growth and self-actualization, this research identifies how AI technologies can influence the development of individuals and the quality of teacher-student relationships. Furthermore, the study explores how Carl Rogers' humanistic philosophy can guide the design of pedagogical practices that prioritize individual needs and experiences. Within this framework, the research examines the potential of AI to support personalized and responsive learning while upholding ethical values and relevant norms. The research also investigates the impact of AI on student assessment and how a humanistic approach can inform efforts to ensure that educational evaluations continue to consider the humane aspects of learning. Overall, this study aims to contribute to the ongoing discourse on the ethical dimensions of AI in education by providing insights from a humanistic philosophy perspective inspired by Carl Rogers. By analyzing the influence of AI on education through this philosophical lens, the study underscores the importance of addressing ethical concerns and promoting human-centered educational practices in the AI era.